TINJAUAN TENTANG KOPEPODA PARASIT DI INDONESIA [A Review of Parasitic Copepods in Indonesia] - Sidabalok, Conni (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Parasitic copepods are of the most important parasites in the marine environment. They occupy a wide range of hosts ranging from many major groups of invertebrates to the top predators in the sea. Indonesia with vast ocean area has great opportunity to harbour a large numbers of parasitic copepods. However, only few studies of parasitic copepods have been conducted in this region, and most of them are preliminary studies, particularly on mariculture associated copepods. To date, only 70 species of parasitic copepods have been recorded from Indonesian waters. There is a lack of taxonomical approach on these studies, in which some of the specimens were not identified to species level.This highlights the need for taxonomic study and even molecular study of marine parasitic copepods in Indonesia. This paper aims to review the evolution of research on parasitic copepods in Indonesia and to identify areas in need of future research.